Effect of surgeon expertise on the outcome in primary hyperparathyroidism - Willeke, Frank; Willeke, Monika; Hinz, Ulf; Lorenz, Dorothea; Nitschmann, Kristian Hans Erhard; Grauer, Andreas; Senninger, Norbert; Klar, Ernst; Herfarth, Christian (Archives of surgery, 1998)
Success in surgery for primary hyperparathyroidism (PHPT) is thought to be closely linked to surgical expertise. We investigated the effect of the surgeon's experience on the postoperative outcome in patients with PHPT.Cohort study with retrospective analysis.University tertiary care center.Two hundred thirty consecutive patients with PHPT. We excluded patients with prior cervical surgery, parathyroid carcinoma, multiple endocrine neoplasia types 1 and 2, and renal hyperparathyroidism.All 230 patients underwent bilateral neck exploration for PHPT.We registered complication rates, fulfillment of predefined operative concepts, and operative time in 230 cervical revisions for PHPT and compared the results of experienced surgeons (40 or more cervical revisions for PHPT performed before 1988) with those of surgeons still in training.Two surgeons classified as experienced operated on 75 patients. Under supervision of these surgeons, most operative procedures (n=155) were performed by 12 different surgeons classified as less experienced. Complications were observed in 31 patients (13.5%) with no statistical difference between the specialists and the less-experienced surgeons (P=.85). The ability to demonstrate 4 or more parathyroid glands was significantly increased for the specialists (74.7% vs 51.6%; P<.001), who also terminated the operation earlier (average, 15 minutes; P<.001).In an analysis of 230 operations for PHPT in patients without prior neck surgery, no effect of the surgeon's experience on postoperative outcome was demonstrated. Under the supervision of experienced endocrine surgeons, less-experienced surgeons perform cervical revisions for PHPT with comparable results, although with longer operating time.-->
Gesehen am 02.10.2025